On/off switching of adhesion in gecko‐inspired adhesives. Issue 2 (5th May 2021) - Yamaguchi, Tetsuo; Akamine, Akira; Sawae, Yoshinori
Abstract: In this study, the adhesion‐detachment behaviour of a gecko‐inspired adhesive pad was investigated to understand the on/off switching mechanisms of adhesion in gecko feet. A macroscopic spatula model was fabricated using silicone rubber, and adhesion tests combining lateral sliding and vertical debonding were conducted. It was observed that the contact state and the adhesion force of the pad vary considerably with the direction of lateral sliding prior to debonding, and that the pad achieves adhesion during debonding even when it loses contact due to excess lateral sliding. These results explain the mechanisms behind the on/off switching and stable adhesion of gecko feet, and suggest the possibility of developing new‐generation adhesives capable of switchable adhesion.